The assessment of static balance in children with hearing, visual and intellectual disabilities - Aija Klavina; Anna Zusa-Rodke; Zinta Galeja (Palacký University Olomouc, 2017)
Background: Balance is a fundamental part of many movement tasks a child performs. Maintaining upright posture is a complex process involving multiple body parts and functional systems. Objective: This study aimed to explore the mean amplitude and velocity of the center of pressure (COP) displacements during static balance tests in children with and without disabilities. Methods: Participants were 34 children (age 8.5 to 10.8 years) including 6 typically developed children, 8 children with hearing, 8 children with visual and 12 children with intellectual disabilities. Static balance data were obtained in 15 s bipedal stance with eyes open and eyes closed, and also in 10 s unipedal stance. A force plate was used to collect data of COP amplitude in anterior-posterior (COPA-P), medio-lateral (COPM-L) directions and COP velocity (COPV). Results: Study outcomes revealed that all subgroups presented larger COP displacement and velocity with eyes closed (p < .001). During bipedal stance with eyes open for results of COPM-L and COPV no significant differences were found between children with and without disabilities (p > .05). Children with intellectual and visual impairments presented significantly larger displacement in COPA-P and COPM-L in comparison with children with hearing impairment and without disability (p < .05). Conclusions: This study provided evidence of comparative outcomes on static stability assessment in elementary school children with and without disability. While in many test items children with disability did not demonstrate a significantly decreased level of postural control outcomes comparing to their peers without disability, the balance assessment should be used for early detection of dysfunction in children, so as to guide the application of appropriate intervention.